MODELING OF WATER QUALITY IN THE PAMPANG RIVER, MAKASSAR CITY, USING THE QUAL2KW APPLICATION: PEMODELAN KUALITAS AIR SUNGAI PAMPANG KOTA MAKASSAR DENGAN MENGGUNAKAN APLIKASI QUAL2Kw - Muh Syawal; Akrim, Djusdil; Jumadil; Anggraini, Nani (Program Studi Teknik Lingkungan Universitas Bosowa, 2025)
The Pampang River is a tributary of the Tallo River that plays an important role as a source of clean water, irrigation, and support for community activities in Makassar City and its surroundings. However, increased industrial and residential activities around the river have caused a decline in water quality. This study aims to determine the water quality conditions of the Pampang River and analyze the distribution pattern of pollutants using the QUAL2Kw application. The research method involved collecting water samples at several points, followed by analysis of water quality parameters, including Total Suspended Solids (TSS), Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), pH, Total Coliform, and E. Coli. The results of the study show that several water quality parameters still meet quality standards, such as TSS, pH, Total Coliform, and E. Coli. However, the DO, BOD, and COD parameters exceed the established quality standards, indicating a fairly high organic pollutant load in the Pampang River. Modeling results using QUAL2Kw show that water quality fluctuations are influenced by daily changes in conditions, such as temperature and sunlight intensity, which affect dissolved oxygen concentrations and the decomposition of organic matter. This study is expected to serve as a reference for the government and the community in their efforts to manage and control pollution in the Pampang River, as well as to support strategic planning to maintain the sustainability of water quality.